2011
DOI: 10.1093/tropej/fmq122
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Plasminogen Activator Inhibitor-1 and Decrease of Transforming Growth Factor-B1 in Children with Dengue Haemorrhagic Fever in Indonesia

Abstract: Mortality in children with severe dengue haemorrhagic fever (DHF) in Indonesia is high. The origin of the elevated plasminogen activator inhibitor-1 (PAI-1) levels in these children is unclear. We measured PAI-1, transforming growth factor-β1 (TGF-β1), platelet counts, plasma leakage and liver function in 71 children with DHF (3-15 years old) and in 30 healthy children. We found that PAI-1 concentrations in children with DHF were significantly higher on admission than on Day 2. Circulating TGF-β1 concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Interestingly, none of them found a correlation between elevated levels of PAI-1 and disease severity. However, both elevated PAI-1 levels and disease severity did correlate with poor clinical outcome and platelet count (43)(44)(45). Additionally, it has been demonstrated that the EIII domain of the DENV2 E protein induces PAI-1 gene expression (46).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, none of them found a correlation between elevated levels of PAI-1 and disease severity. However, both elevated PAI-1 levels and disease severity did correlate with poor clinical outcome and platelet count (43)(44)(45). Additionally, it has been demonstrated that the EIII domain of the DENV2 E protein induces PAI-1 gene expression (46).…”
Section: Discussionmentioning
confidence: 99%
“…PAI-1 values correlated well with platelet counts, plasma leakage, serum albumin on admission and the degree of pleural effusion. There was no correlation between mildly elevated liver function tests and PAI-1 levels [12].…”
Section: Plasminogen Activator Inhibitormentioning
confidence: 73%
“…The existing laboratory tests to monitor abnormal host response [10][11][12] are complex, costly and require sophisticated laboratory infrastructure and trained personnel. Researchers should standardize 1-2 step in vitro assays which can be carried out in non-academic, non-research health centres.…”
Section: Point-of-care Assays Of Abnormal Host Factors In Denv Infectmentioning
confidence: 99%
“…Elevated PAI-1 concentration in children suffering from dengue hemorrhagic fever was also reported [3,31,32]. In addition, a recent study on Ebola virus infection showed that PAI-1 levels were elevated in pediatric patients, and were strongly elevated in patients who died and in those with hemorrhagic manifestations [33].…”
Section: Discussionmentioning
confidence: 86%